The dopamine effect on sea urchin larvae depends on their age. (2nd February 2023) - Kalachev, Alexander V.; Tankovich, Alina E.
Abstract: Activation of the dopamine type‐D2 receptor in late gastrula of sea urchins is known to decrease the growth rate of post‐oral arms of larvae, and, as a result, the phenotype of these larvae mimics that of larvae developing in the abundance of food. Our data indicate that the effect of dopamine on sea urchin larvae is stage‐dependent. In our experiment, the early four‐armed plutei (96 hours post fertilization, hpf) of Strongylocentrotus intermedius had substantially shorter post‐oral arms if they developed from the larvae treated with dopamine at the early pluteus stage (48 hpf), when they had already formed the first dopaminergic neurons, as compared to the plutei from the larvae treated with dopamine at the mid to late gastrula stage (24 hpf), when they did not have any neurons yet. The pre‐treatment of larvae in 6‐hydroxydopamine, a neurotoxic analog of dopamine that specifically disrupts activity of dopaminergic neurons, prevented the development of the short post‐oral arms phenotype in larvae. These results confirm the assumption that dopaminergic neurons play an important role in the development of the short post‐oral arms phenotype in sea urchin larvae. Another finding of our study is that the dopamine treatment also affects the growth of the body rods and the overall larval body growth. Based on these observations, we suggest researchers to carefully select the developmental stage, pharmacological agents, and incubation time for experimental manipulation of sea urchin larvae phenotypes through dopaminergic nervous system. Abstract : Our data indicate that the effect of dopamine on sea urchin larvae is stage‐dependent. The early four‐armed plutei (96 h post fertilization, hpf) of Strongylocentrotus intermedius had substantially shorter post‐oral arms if they developed from the larvae treated with dopamine at the early pluteus stage (48 hpf), when they had already formed the first dopaminergic neurons, as compared to the plutei from the larvae treated with dopamine at the mid to late gastrula stage (24 hpf), when they had not had any neurons yet. The pre‐treatment of larvae in 6‐hydroxydopamine, a neurotoxic analog of dopamine that specifically disrupts activity of dopaminergic neurons, prevented the development of the short post‐oral arms phenotype in larvae.